1998
DOI: 10.1107/s0021889897012727
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a New Boron-Rich Phase by Electron Crystallography

Abstract: In examining a supply of supposedly amorphous, highpurity, boron powder, a significant proportion of the particles were found to be well crystallized. Examination of these crystalline particles by convergent-beam electron diffraction revealed that they were orthorhombic with space group Pnma (a = 16.7, b = 17.7, c = 10.3 A,). Contaminating impurities are thought to be responsible for the formation of this crystal structure but the authors were unable to identify them by analytical transmission electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The d-spacings and intensities were consistent with those of α-rhombohedral phase of boron, but the possibility of amorphous boron was not ruled out. Steeds and Wilson (1998) examined an amorphous boron sample and observed that a significant proportion of the particles were well crystallized in that sample. Examination of these crystalline particles by convergent beam electron diffraction technique revealed that they were orthorhombic with space group Pnma.…”
Section: Introductionmentioning
confidence: 99%
“…The d-spacings and intensities were consistent with those of α-rhombohedral phase of boron, but the possibility of amorphous boron was not ruled out. Steeds and Wilson (1998) examined an amorphous boron sample and observed that a significant proportion of the particles were well crystallized in that sample. Examination of these crystalline particles by convergent beam electron diffraction technique revealed that they were orthorhombic with space group Pnma.…”
Section: Introductionmentioning
confidence: 99%